EFFECT OF ADHESIVE ON THE SHAPE MEMORY BEHAVIOUR OF THERMOPLASTIC POLYURETHANE - XU, WENSEN (My University, 2015)
Taking advantage of their inherent abrasion resistant, weather resistant, and outstanding mechanical strength, film-grade thermoplastic polyurethanes (TPU) are currently being used as paint protective films but are also being considered for paint replacement within the automotive industry. Special grades of TPU with shape memory behaviour offer an additional feature of self-healing to decorative coatings but there are concerns of shape fixity at service temperatures which are above their glass transition temperature (Tg). In this study, the shape memory behaviour of a developmental TPU film with Tg around room temperature was investigated. In order to understand the shape memory behaviour, the TPU film was laminated to a rigid polymer substrate of either polypropylene (PP) or acrylonitrile butadiene styrene (ABS). Three different acrylic based pressure sensitive adhesives were tested to bond the film to the substrate, namely a commercial high shear strength transfer tape and two solvent based adhesives of high and low shear strength that were manually cast. The influence of the adhesive was given significant attention as a variable of study in this thesis. The characterization of all the polymeric films and substrates was based on a series of thermo-mechanical tests (tensile test, stress relaxation test, DSC and DMA). The adhesives were characterized by lap-shear test, peel test, and parallel plate rheometry. The results of material characterization were used to support the analysis and interpretation of shape memory behaviour. The TPU based laminate was deformed by a matched mold thermoforming process with a pair of arched matched molds. The recovery behaviour of formed samples was quantified with a newly designed measurement method and the results were reported as recovery ratio and recovery rate. During recovery, the surrounding temperature was considered to be an important variable. The recovery behaviour of specimens was investigated in a controlled environment at setpoint temperatures of 15oC, 45oC or 65oC. No shape memory effect was found at 15oC (below TPU’s Tg), and yet both recovery ratio and recovery rate increased with temperature, from 45oC to 65oC (both above the TPU’s Tg). Since the recovery process was related to the elastic response of the hard segment phase within the TPU, the recovery stress was strongly related to strain conditions. By varying the draw depth into the mold from 6 mm, to 10 mm or 12 mm (8.86%, 15.90% or 19.88% strain, respectively), the recovery measurement results showed that the shape memory effect was weaker with lower strain as less recovery stresses were generated in the TPU film. With the draw depth of 10 mm, the highest recovery ratio and recovery rate were observed, and yet an inexplicable decrease in the recovery ratio and recovery rate occurred as the draw depth increased further from 10mm to 12mm. In regards to the influence by a substrate, TPU/PP laminate showed a more significant recovery behaviour than TPU/ABS laminates at both 45oC and 65oC. The elastic modulus of the substrate was found to have a key role on the recovery process; the recovery nature of formed laminate decreased with stiffer substrate. Three adhesives with differing rheological and adhesion properties were tested to bond the TPU film to a substrate. The formed laminates with “strongest” adhesive (transfer tape) in terms of stiffness and adhesion strength showed the highest recovery ratio/rate over laminates made with “weaker” solvent cast adhesives, at both 45oC and 65oC. A finite element analysis (FEA) was employed to simulate the stress transfer within a multilayer structure bonded by a viscoelastic adhesive layer of varying stiffness; the simulated result showed that the relatively low stiffness adhesive could reduce the stress transfer efficiency within layers of a laminate. It suggested that more recovery stresses were transferred from TPU to substrate with a stiffer adhesive layer (transfer tape) and hence increased the recovery ratio and recovery rate. Therefore, adhesive with relatively low stiffness and adhesion strength could be a better choice to reduce the recovery effect of TPU laminate after forming. However, TPU was found to slide at the unsealed edge of formed laminate when the solvent based adhesives were used; the sliding behavior reduced the recovery by releasing stored recovery stress. In the case of HS and LS adhesives at high temperature (65oC), cohesive failure was observed when the edge of specimen was sealed led to a higher bending moment thus increased the recovery ratio over 24 hours investigations. Therefore, adhesives of weaker shear strength do not necessarily overcome the nature of shape recovery by the TPU when formed part shape needs to be preserved.
EFFECT OF ADHESIVE ON THE SHAPE MEMORY BEHAVIOUR OF THERMOPLASTIC POLYURETHANE UNDER VARYING CONDITIONS
Keywords: Shape memory polymer; Thermoplastic Polyurethane; Polymer Laminate; Adhesives